Interest of Pet Imaging in Multiple Myeloma - Jamet, Bastien; Bailly, Clément; Carlier, Thomas; Touzeau, Cyrille; Nanni, Cristina; Zamagni, Elena; Barré, Louisa; Michaud, Anne-Victoire; Chérel, Michel; Moreau, Philippe; Bodet-Milin, Caroline; Kraeber-Bodéré, Françoise (Frontiers in Medicine, 2019)
The interest of 18Fluoro-deoxyglucose (FDG) positron emission tomography (PET) imaging in the management of patients with multiple myeloma (MM) for the workup at diagnosis and for therapeutic evaluation has recently been demonstrated. FDG-PET is a powerful imaging tool for bone lesions detection at initial diagnosis with high sensitivity and specificity values. The independent pejorative prognostic value on progression-free survival (PFS) and overall survival (OS) of baseline PET-derived parameters (presence of extra-medullary disease (EMD), number of focal bone lesions (FLs) and maximum standardized uptake values (SUVmax)) has been reported in several large independent prospective studies. During therapeutic evaluation, FDG-PET is considered as the reference imaging technique, because it can be performed much earlier than MRI which lacks specificity. Persistence of significant FDG uptake after treatment, notably before maintenance therapy, is an independent pejorative prognostic factor, especially for patients with a complete biological response. So FDG-PET and medullary flow cytometry are complementary tools for detection of minimal residual disease before maintenance therapy. However, the definition of PET metabolic complete response should be standardized. In patients with smoldering multiple myeloma, the presence of at least one hyper-metabolic lytic lesions on FDG-PET may be considered as a criterion for initiating therapy. FDG-PET is also indicated for initial staging of a solitary plasmacytoma so as to not disregard other bone or extra-medullary localizations. Development of nuclear medicine offer new perspectives for MM imaging. Recent PET tracers are willing to overcome limitations of FDG. (11)C-Methionine, which uptake reflects the increased protein synthesis of malignant cells seems to correlate well with bone marrow infiltration. Lipid tracers, such as Choline or acetate, and some peptide tracers, such as (68) Ga-Pentixafor, that targets CXCR4 (chemokine receptor-4, which is often expressed with high density by myeloma cells), are other promising PET ligands. 18F-fludarabine and immuno-PET targeting CD138 and CD38 also showed promising results in preclinical models.